Coalesced thermal and electrotransfer mediated delivery of plasmid DNA to the skin - Bulysheva, Anna (Bioelectrochemistry, 2018)
Efficient gene delivery and expression in the skin can be a promising minimally invasive technique for therapeutic clinical applications for immunotherapy, vaccinations, wound healing, cancer, and peripheral artery disease. One of the challenges for efficient gene electrotransfer (GET) to skin in vivo is confinement of expression to the epithelium. Another challenge involves tissue damage. Optimizing gene expression profiles, while minimizing tissue damage are necessary for therapeutic applications. Previously, we established that heating pretreatment to 43 °C enhances GET in vitro. We observed a similar trend in vivo, with an IR-pretreatment for skin heating prior to GET. Currently, we tested a range of GET conditions in vivo in guinea pigs with and without preheating the skin to ~43 °C. IR-laser heating and conduction heating were tested in conjunction with GET. In vivo electrotransfer to the skin by moderately elevating tissue temperature can lead to enhanced gene expression, as well as achieve gene transfer in epidermal, dermal, hypodermal and muscle tissue layers.